2021
DOI: 10.4097/kja.19493
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with hypotensive bradycardic events during open shoulder surgery in the beach chair position

Abstract: Background: Shoulder surgery in the beach chair position frequently causes hypotensive bradycardic events (HBEs), which are potentially associated with an increased risk of cerebral hypoperfusion. Here, we aimed to investigate the incidence and characteristics of symptomatic HBEs that require pharmacological interventions, and to identify specific risk factors associated with symptomatic HBEs. Methods: We retrospectively examined the records of all patients aged ≥ 18 years who underwent shoulder arthrotomy in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Our results may suggest that HBEs cannot be separated from various other types of syncopal reaction. However, preoperative ISB was reported as one of the risk factors associated with HBEs in a recent study of open shoulder surgery [ 23 ]. Further studies are thus needed before a definite conclusion can be drawn about the impact of the ISB on HBEs.…”
Section: Discussionmentioning
confidence: 99%
“…Our results may suggest that HBEs cannot be separated from various other types of syncopal reaction. However, preoperative ISB was reported as one of the risk factors associated with HBEs in a recent study of open shoulder surgery [ 23 ]. Further studies are thus needed before a definite conclusion can be drawn about the impact of the ISB on HBEs.…”
Section: Discussionmentioning
confidence: 99%
“…[38] In another study, pre-operative interscalene brachial plexus (BP) block and advanced age were risk factors associated with symptomatic hypotensive bradycardic events in the beach chair position. [39] The beach chair position angle was shown to affect cerebral oxygenation, and there was a linear decline in cerebral oxygenation as the position angle increased. [40] The current recommendations suggest that beach chair and lateral position are safe and successful methods for patient positioning in shoulder arthroscopic procedures without conclusive evidence of superiority of one position to the other.…”
Section: Anesthesia and Positioning In Shoulder Arthroscopymentioning
confidence: 99%
“…In particular, there is the possibility of a serious side effects of compromised cerebral perfusion in the beach chair position by which improves intra-articular visualization during arthroscopic surgery. Choi et al [6] showed that symptomatic hypotensive bradycardia occurred in 60% of all shoulder surgeries with the beach chair position and that preoperative interscalene brachial plexus block and old age were risk factors for symptomatic hypotensive bradycardia. During shoulder arthroscopy, hypothermia is common and can be contributed by the irrigation of the shoulder joint, impaired thermoregulation, and vasodilation due to anesthesia.…”
mentioning
confidence: 99%
“…Lee et al [8] found that perioperative hypothermia was more prevalent in general anesthesia than in interscalene brachial plexus block combined with propofol sedation. They also showed that there was no difference in the incidence of hypothermia between the elderly and younger patient groups.From these retrospective studies [4,6,8], it is thought that elderly patients with comorbidities are unlikely to be discharged on the same day and are at an increased risk of readmission in the setting of ambulatory shoulder surgery. Old age may also be associated with a high risk of hypotensive bradycardia, particularly in the beach chair position.…”
mentioning
confidence: 99%
See 1 more Smart Citation